Pemanfaatan Limbah Plastik menjadi Eco-Conblock sebagai Upaya Peningkatan Kapasitas Lokal dan Pemberdayaan Masyarakat Desa Ponggang - Satria Kusuma Fajar Mahardika; Enny Widawati; Yusak Sutikno; Almendo Patar Ibouto Gobai; Gandhes Larasati; Angelica Putri Arista; Silvester Julio Xavier; Gabriel Rodo Oloanki Simanjorang; Louis Putra Purnama (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
As a tourism village, Ponggang faces problems related to waste management that are currently not being handled properly. If not followed up, this will pose a threat to both public health and the potential for damage to the village's natural and environmental attractions. Therefore, this community service aims to empower community groups through the utilization of plastic waste into products with higher economic value (eco-conblock). The methods used in this service include outreach activities aimed at increasing awareness and understanding of partners about the concept of village tourism and training/mentoring activities that involve the active role of community members aimed at increasing technical skills and waste management governance. From the evaluation results, it can be seen that the aspect of community awareness and understanding of good waste management has significantly increased from 3.85 points (good) to 4.47 points (very good). Meanwhile, the aspect of skills and governance has increased significantly on average from 3.39 points (moderate) to 3.68 points (good). In addition, the community service program has also succeeded in building an integrated waste management facility that can later be used sustainably towards Ponggang becoming an independent tourism village.